The long-term effect of a protein-deficient-diet enriched with vitamin B6 on the blood parameters in unexercised and exercised rats - Sławomir Lewicki (Taylor & Francis Group, 2018)
Protein undernutrition affects inter alia blood parameters and immune system. These negative effects may be improved by the addition of vitamin B6 to the diet. Here, we evaluated the effect of vitamin B6 supplementation and physical exercise in rats fed a protein-deficient diet. Rats were divided into six groups: exercised or unexercised – control, protein deficient, protein deficient with vitamin B6 supplementation. Sixty days of protein malnutrition caused significant changes in the rat body weight, haematological parameters (mainly red blood cells parameters), immunological parameters (NK and NKT cells) and biochemical parameters (total protein and albumin concentration and activity of AST). The rat exercise did not intensify the negative effects of protein malnutrition. The vitamin B6 supplementation in protein-deficient groups significantly improved body weight and red blood cell parameters. These results indicate that vitamin B6 should be considered as a valuable supplement for individuals suffering from protein malnutrition.